KAJIAN HUKUM ATAS PENGENAAN BPHTB DAN PPH FINAL PENGALIHAN HAK ATAS TANAH DAN BANGUNAN DALAM TRANSAKSI BOT (BUILT OPERATE AND TRANSFER) - DINA ARFINA (PREMISE LAW JURNAL, 2015)
Built, Operate and Transfer (BOT) is the financing for a construction project in which the investor should himself prepare the project financing. He should also be responsible for preparing the materials, equipment, and other facilities which are needed for the project equipment. The compensation is that he will be given the right to operate and to benefit its economy in a certain time. Cooperative agreement by using BOT system is not only between the government and private sector but also between non-government and private sector. There is no obstacle in BOT agreement between the government and private sector in levying BPHTB and Final PPh (income tax) on land and building rights transfer, while obstacle in the same case is found in BOT agreement between non-government and private sector; the obstacle is also found in levying BPHTB and Final PPh on the land and building rights transfer in BOT transaction.The judicial obstacle is that there is no specific regulation on BOT transaction in Article 85, paragraph 1 and paragraph 2 of PDRB law as taxable item in levying BPHTB and Final PPh on land and building rights transfer, while Final PPh on land and building rights transfer is levied tax payable as it is stipulated in the provision of the Decree of the Minister of Finance No. 635/KMK.04/1994 as it is finally amended to the Regulation of the Minister of Finance No. 243/PMK.03/2008. Keywords: Transfer Use Building, BOT, Tax, PPh, BPHTB